The Impact of Director’ Leadership, Educational Environment, Teacher Efficacy and Extracarricular Sports Programs on Job Satisfaction of Kindergarten Teachers - Jong-Taek Seo,; Ju-Kyoung Kim,; Bok-Nyong Park,; Young-gi Kim,; Hee-Lee, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The role of kindergarten teachers as a viable alternative to childcare is becoming increasingly important due to the rising amount of time children spend in educational institutions compared to the time, they spend with their parents in the home environment. The primary aim of this research is to assess the influence of directorial leadership, the educational environment, teacher efficacy, and extracurricular programmes on the level of job satisfaction experienced by kindergarten teachers. This study includes a sample size of 256 kindergarten teachers. The research findings were subjected to analysis using Smart PLS 4 software, employing the Partial Least Squares (PLS) algorithm and the Bootstrapping method. The findings of the empirical study indicate a positive correlation between the leadership of directors, the educational environment, teacher efficacy, and extracurricular programmes with the job satisfaction of kindergarten teachers. This study holds both theoretical and practical significance, as its findings demonstrate the potential to enhance the working environment for teachers responsible for primary childhood education. Additionally, it provides fundamental data that can contribute to the improvement of children's learning abilities and offers a foundation for policymaking that takes into account the health education of teachers.